MULTIVARIATE ANALYSIS FOR ELEMENTAL COMPOSITION AMONG INDIGENOUS COMMON BUCKWHEAT GENOTYPES OF BALTISTAN - I. Hussain; 2; A. Bano; Faizanullah; A. Nosheen (Journal of Animal and Plant Sciences, 2016)
Macro and microelements play fundamental role in the metabolic reactions required for growth and development. Buckwheat being used for medicinal purpose may be an important source of essential minerals and nutrients for rural communities of Pakistan. The present study was aimed to investigate elemental composition in flour samples of twelve indigenous genotypes grown in Pakistan (Baltistan) by using multivariate approach. After acid digestion, samples were subjected to atomic absorption spectrophotometry and data were analyzed statistically for basic statistics and principal component analysis (PCA). Local genotype BWB-4 showed highest P and Ca level (430±4.07 and 33.91±0.31 mg/100g respectively). On the other hand genotype BWA-7 recorded highest levels of Fe and Zn (2.9±0.03 and 4.5±0.08 mg/100 g respectively). PCA extraction exhibited nine main principal components, where maximum variation was shown by the first two components (50.63%). Maximum contribution was made by genotypes with larger seed size viz. BWSN-5 followed by BWA-7 and BWZ-8. For major and trace elements the 1st component revealed a major group among all local genotypes for P and Co whereas 2nd component showed Mn as main element with greater factor loadings. Variations in the elemental composition by using multivariate analysis like PCA proved to be a suitable tool for identification of potential genotypes for future breeding programs.
Keywords: Buckwheat; major and trace elements; PCA; genotypes; Pakistan